2007
DOI: 10.3346/jkms.2007.22.s.s38
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lewis Lung Carcinoma Growth by Toxoplasma gondii through Induction of Th1 Immune Responses and Inhibition of Angiogenesis

Abstract: Toxoplasma gondii is an obligate intracellular protozoan parasite that induces antitumor activity against certain types of cancers. However, little information is available regarding the immunologic mechanisms that regulate these effects. For this purpose, C57BL/6 mice were administered either the T. gondii Me49 strain orally or Lewis lung carcinoma (LLC) cells intramuscularly. Survival rates, tumor size, histopathology, and immune responses were determined for each group, and angiogenesis was evaluated by in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 26 publications
4
84
0
1
Order By: Relevance
“…Important clues indicate that LXs, the first family of endogenous "braking signals" in inflammation identified in vivo (5), might interfere with tumor angiogenesis (16,17). HCC is a highly vascular tumor, and angiogenesis is believed to play a crucial role in its development (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important clues indicate that LXs, the first family of endogenous "braking signals" in inflammation identified in vivo (5), might interfere with tumor angiogenesis (16,17). HCC is a highly vascular tumor, and angiogenesis is believed to play a crucial role in its development (32).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it was recently identified that tumor growth was inhibited concomitantly with suppressed angiogenesis during acute Toxoplasma gondii infection in mice (16,17). These observations suggest that LXs might be involved in tumor angiogenesis, but the governing mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 96%
“…According to previous researches, some parasites have capability of antitumor activities (Darani and Yousefi 2012;Kim et al 2007;López et al 2010;Oikonomopoulou et al 2013;Pidherney et al 1993;Plumelle et al 1997) and so parasite antigens have been considered as possible targets for cancer immunotherapy (Darani and Yousefi 2012). In a retrospective study with a large population it has been shown that the prevalence of hydatid cysts in patients with cancer was significantly lower than the control group (Akgül et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors such as air pollution and dietary habits may be responsible for the increase in the cancer mortality following control of infectious and parasitic diseases. However, there are raising scientific evidences indicating that parasitic or bacterial infections induce antitumor activity against certain types of cancers [3][4][5][6][7][8]. For example, anticancer activity of Trypanozoma cruzi parasites has been demonstrated [3], and it has been shown that Bacillus Calmette Guerin (BCG) is an effective immunotherapy for carcinoma of the bladder, as reviewed by Herr et al [8].…”
mentioning
confidence: 99%